Preconcentration and determination of mercury(II) at a chemically modified electrode containing 3-(2-thioimidazolyl)propyl silica gel - Dias Filho, Newton L. [UNESP]; Do Carmo, Devaney R. [UNESP]; Caetano, Laércio [UNESP]; Rosa, André H. [UNESP] (Springer Nature, 2005)
A mercury-sensitive chemically modified graphite paste electrode was constructed by incorporating modified silica gel into a conventional graphite paste electrode. The functional group attached to the (3-chloropropyl) silica gel surface was 2-mercaptoimidazole, giving a new product denoted by 3-(2-thioimidazolyl)propyl silica gel, which is able to complex mercury ions. Mercury was chemically adsorbed on the modified graphite paste electrode containing 3-(2-thioimidazolyl)propyl silica (TIPSG GPE) by immersion in a Hg(II) solution, and the resultant surface was characterized by cyclic and differential pulse anodic stripping voltammetry. One cathodic peak at 0.1 V and other anodic peak at 0.34 V were observed on scanning the potential from -0.1 to 0.8 V (0.01 M KNO3; ν = 2.0 mV s-1 νs. Ag/AgCl). The anodic peak at 0.34 V show an excellent sensitivity for Hg(II) ions in the presence of several foreign ions. A calibration graph covering the concentration range from 0.02 to 2 mg L-1 was obtained. The detection limit was estimated to be 5 μg L-1. The precision for six determinations of 0.05 and 0.26 mg L-1 Hg(II) was 3.0 and 2.5% (relative standard deviation), respectively. The method can be used to determine the concentration of mercury(II) in natural waters contaminated by this metal. 2005 © The Japan Society for Analytical Chemistry.
Keywords: 2 imidazolidinethione; 2-mercaptoimidazole; cation; drug derivative; fresh water; graphite; imidazole derivative; mercaptoimidazole; mercury; sea water; silica gel; silicon dioxide; calibration; chemistry; electrochemistry; instrumentation; ion selective electrode; methodology; oxidation reduction reaction; pH; reproducibility; Calibration; Cations; Electrochemistry; Ethylenethiourea; Fresh Water; Graphite; Hydrogen-Ion Concentration; Imidazoles; Ion-Selective Electrodes; Mercury; Oxidation-Reduction; Reproducibility of Results; Seawater; Silicon Dioxide